Hubungan Kepemimpinan Transaksional Preseptor Akademik Terhadap Kinerja Praktik Mahasiswa Keperawatan Universitas Malahayati Bandar Lampung - Ni Luh Sumo; M. Arifki Zainaro; Dewi Kusumaningsih (Universitas Malahayati Lampung, 2025)
ABSTRACT Transactional leadership style is one of the factors that can improve the practical performance of nursing students. This leadership approach is needed to support the learning and development of nursing students. This research aims to explore and analyze the relationship between academic preceptor transactional leadership and student practical performance nursing. By understanding the dynamics and influence of this type of leadership, it is hoped that it can provide in-depth insight into other factors that can influence nursing students' practical performance. It is known that there is a relationship between the transactional leadership style of academic preceptors and the practical performance of nursing students in the field. This research uses a quantitative type of research. Quantitative research uses an analytical survey approach with cross-sectional methods. The population of this study was 247 students from the Malahayati University nursing study program. The sample used was 229 respondents. The results of the analysis show that the majority of academic preceptors have low transactional leadership, and the majority of practical students' performance is poor, p-value 0.001 (0.05). There is a relationship between the transactional leadership of academic preceptors and students' practical performance. Keywords : Leadership Style, Transactional, Practical Performance ABSTRAK Gaya kepemimpinan transaksional merupakan salah satu faktor yang dapat meningkatkan kinerja praktik mahasiswa keperawatan pendekatan kepemimpinan ini diperlukan dalam mendukung pembelajaran dan pengembangan mahasiswa keperawatan. Penelitian ini bertujuan untuk mengeksplorasi dan menganalisis hubungan antara kepemimpinan transaksional preseptor akademik dengan kinerja praktik mahasiswa keperawatan. Dengan memahami dinamika dan pengaruh dari jenis kepemimpinan ini, diharapkan dapat memberikan wawasan yang mendalam mengenai faktor lain yang dapat mempengaruhi kinerja praktik mahasiswa keperawatan. Diketahui adanya hubungan gaya kepemimpinan transaksional preseptor akademik terhadap kinerja praktik mahasiswa keperawatan di lapangan. Penelitian ini menggunakan jenis penelitian kuantitaif. penelitian kuantitatif menggunakan pendekatan survey analitik (analytical survey) dengan metode crosssectional. Populasi penelitian ini berjumlah 247 mahasiswa Program Studi Ilmu Keperawatan Universitas Malahayati. Sampel yang digunakan 229 responden. Hasil analisis menunjukan sebagian besar preceptor akademik dengan kepemimpinan transaksional yang rendah, dan Sebagian besar kinerja mahasiswa praktik kurang baik, p-value 0,001 (0,05). Ada hubungan antara kepemimpinan transaksional preseptor akademik terhadap kinerja praktik mahasiswa. Kata Kunci : Gaya Kepemimpinan, Transaksional, Kinerja Praktek